2022
DOI: 10.1002/jcop.22876
|View full text |Cite
|
Sign up to set email alerts
|

Delivering a psychosocial program for older people living in retirement homes during the Covid‐19 pandemic: A process evaluation and recommendations for community interventions

Abstract: The Covid‐19 pandemic lockdown regulations caused retirement homes to temporarily ban in‐person visitation potentially increasing the mental health risks of older people. An opportunity arose for a multistakeholder community collaboration to design a mental health program for older people. To evaluate the process of delivering a 12‐week psychosocial program aimed at preventing loneliness, countering boredom, and providing older people in restricted settings with education about Covid‐19 during the lockdown, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The lockdown's negative effects were observed across NHs, affecting residents, families, caregivers, and mental health professionals. Finally, the international literature seems to support the same conclusions as our article within the studied populations (9)(10)(11)(26)(27)(28)(29). Tailored regional support aligned with NH characteristics is imperative, including training mental health professionals in coping strategies and psychosocial interventions (27).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The lockdown's negative effects were observed across NHs, affecting residents, families, caregivers, and mental health professionals. Finally, the international literature seems to support the same conclusions as our article within the studied populations (9)(10)(11)(26)(27)(28)(29). Tailored regional support aligned with NH characteristics is imperative, including training mental health professionals in coping strategies and psychosocial interventions (27).…”
Section: Discussionsupporting
confidence: 77%
“…Suggestions for targeted interventions may involve offering psychological support techniques to professionals, establishing a supportive culture, regular emotional monitoring, and involving psychologists trained in evidence-based therapies, such as Cognitive and Behavioral Therapies (CBT). These interventions could encompass ongoing training programs for healthcare staff, or older adult ( 29 ), aiming to develop specific skills in emotional management and psychological support to address the unique challenges encountered in care facilities. Implementing protocols to foster an organizational culture that encourages the expression of emotions and peer support could also be a promising intervention approach.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature the authors identified only one South African study reporting on a creative example of service delivery to address mental health risks, including the prevention of loneliness and boredom among older persons during COVID-19 (Jarvis et al, 2022). This population of older persons resided in Durban, and all were in residential care.…”
Section: Social Welfare Services For South African Older Persons Duri...mentioning
confidence: 99%